Defense energy resilience lessons from ecology - Thomas, Scott; Kerner, David (The Letort papers, 2010)
National security relies heavily on the ready availability of energy resources in the types, quantities, and locations the military demands. While U.S. energy needs are currently met, the shrinking gap between global supply and demand draws the world closer to a tipping point at which human behavior is less predictable, competition overwhelms social and geopolitical normalizing forces, and conflict becomes more likely and more pronounced. Given concerns about future resource availability, DoD would be well served by devising and implementing a sustainable, resilient energy strategy that addresses current projections and adapts to evolving conditions